Temperature and Oxygen at Lake Erken, 1940-2015 - Temperature and Oxygen at Lake Erken 1940-2015 - Department of Ecology and Genetics, Uppsala University (Uppsala University, 2018)
Long-term monitoring measurements of temperature profile and oxygen in Lake Erken 1940-2015, colected by The Erken laboratory.

The Erken laboratory is located by the shore of lake Erken, 70 km northeast of Stockholm. A substantial lake measurement program has been running for the last 30 years, which includes manual sampling along with high frequency automatic measurements.

Long-term monitoring measurements of temperature profile and oxygen in Lake Erken 1940-2015.

The data is free to use, but please inform us, so that we can keep track about the projects that make use of our data.

Långsiktiga mätningar av temperaturprofil och syre i Erken 1940-2015, utförda av Erkens monitoringprogram.

Erkenlaboratoriet är belägen vid stranden av sjön Erken, 70 km nordost om Stockholm. Stationen bedriver sedan ungefär 30 år tillbaka ett omfattande miljöövervakningsprogram av sjön Erken, som inkluderar manuella mätningar och högfrekventa automatiska mätningar.

Långsiktiga mätningar av temperaturprofil och syre i Erken 1940-2015.

Det är fritt fram att använda data från vårt monitoringprogram, men vi vill att ni som använder datat ska informera oss så att vi kan hålla reda på vilka projekt som utnyttjar Erkens monitoringprogram.
Temperatur och syre vid sjön Erken, 1940-2015 - Temperatur och syre vid sjön Erken 1940-2015
Keywords: LAKE/POND; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser